Statistical analysis of the word zakat and its application in sahih al-Bukhari’s perspective / Ikmal Hafiz Jamal … [et al] - Jamal, Ikmal Hafiz; Abd Wakil, Muhammad Najib; Yahaya, Muhammad Hasif; Ismail, Ahmad Thaqif; Md Ismail, Mohamad Afandi (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2020)
Several past studies have reported that the awareness of the Muslim community towards zakat and its application remains at a low level. Past studies also found that it is due to the lack of understanding among the community towards the concept of zakat itself. Studies have suggested some solutions to that by proposing different discussions from many perspectives. This study also focuses on that issue; however, from a different perspective. This study focuses on statistically investigating the occurrence of the word zakat as appeared in sahih al-Bukhari. It is to explore the embedded knowledge related to the word zakat from sahih al-Bukhari’s perspective as the most authentic book of hadith. This can be considered as an endeavor to contribute to a zakat related corpus. This is a qualitative research which employs a thematic analysis approach in analyzing the word zakat in sahih al-Bukhārī. Several phases were identified started with the process of extracting the word zakat and ended with analyzing the word. The result obtained shows that the word zakat from sahih al-Bukhari’s perspective can be discussed in several themes. The themes are the aggregation of the word, its linguistic, and hadith related notion.